(3GdCQHYhf aj TjhN GdUhajIs - (3CMeO Hf eMeO Hf CMeO Hf YHO GddgHf MaU Hf GdLdjd GdCfUGQj GdeGdjfj GdgQhj, CHh SYO,J (B412 (3g` s
(3ChdgG (B:s
(3PcQ eYQha GdcQNi CHh eMeO YHO GdhgGH Hf eMeO Hf GdMSjf Hf gGfi GdHRGR HHZOGO s
(3BNQgG (B:s
(3ceG Mci Yf HYVge hSFd Yf eSCdI abGd (B: (3dG COQi hdG COQi fUa GdYde abGd fYe dcf gh GdfUa GdCNjQ s
(3ai Chdg QhGjGJ Yf GdeDda hSeGYGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B211s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B362 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B9 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI (B_ (3HOeTb (B((3JUha (B121) s
Keywords: (3GdJGQjNs